(untitled) (Journal of Dhaka Medical College, 2018)
Background: Anemia is regarded as a major risk factor for unfavorable outcome of pregnancy both for the mother and the fetus. Maternal anaemia is a common problem in pregnancy, particularly in developing countries. Aims: To determine the prevalence of anaemia in pregnancy and to find out the haemoglobin level of pregnant women reporting for antenatal checkup among the women reporting for antenatal care in Combined Military Hospital Dhaka. Method: This is a descriptive cross sectional study was done in the antenatal clinic at CMH Dhaka. One eighty four (184) pregnant women attending antenatal clinic at CMH Dhaka including CWC under CMH Dhaka were included for the study. The data were collected from 1st May 2001 to 31st May 2001 at the antenatal clinic, combined Military Hospital. Dhaka where pregnant women reported for antenatal check up. The data were collected by interviewing respondents in different dates & day of the week at different CWC and CMI-I Dhaka. Prior to the interview the respondents were explained clearly the objective of the study and sought their co-operation. The authority of CMH Dhaka was given prior information through issuing letter from AFMI. The respondent was assured on ethical point of view that strict secrecy would be maintained. Data were collected by the following methods: Interview Method; Laboratory Investigation for Hb estimation and Scrutinization of antenatal check up card. Results: A total of 184 pregnant women of them 70 were primi gravida and 114 were multigravida. The prevalence of anaemia as per WHO cutoff points was 56.52% (<11.0 g/dl). The mean age was 24.96 ± 4.49 years. The age groups 20-24 was the maximum. Out of 184 women 104 women was ariaemic. 15-24 age group was more anaemic (57.42%) than the 25-39 age group (55.42%) but the difference was not statistically significant, P>0.05. The prevalence of anaemia was higher in Illiterate (100%), lowest in degree and above level education group (48.48%). The maximum women (64.13%) belong to lowest income group. (Tk 2500-5000) Anaemia was the most common in the lowest income group (60.50%). The prevalence of anaemia was the highest among the family size 6 and above group (75%) and lowest in 2-3 family size group. Anaemia was more prevalent among high parity group (75%) and lowest in ‘0’ parity group (52.28%) but the difference was not statistically significant (P > 0.05). Multigravida were found more anaemic (62.28%) contrast to prirnigravida (47.14%) which was statistically significant (P<0.05). The prevalence of anaemia was less in higher birth interval group but the difference was not statistically significant (P>0.05). About the cultural belief only 33 women were found having cultural belief of avoiding food during pregnancy (17.93%) and anaemia was more prevalent among them (57.57%) but the difference was statistically significant (P>.05). In this study 14.13% women had concomitant illness during pregnancy. In this study 15 women had caesarian section of which 10 were anaemic (75%) and there was one Forcep delivery (non-anaemic). Conclusion: In this study anaemia is more prevalent among younger age group women (15-24), with less educated group low income group, large family size group, high parity and high gravida, less birth spacing and also in women having concomitant illness. Anaemia is more prevalent among women having cultural belief on avoiding food during pregnancy. The findings of this study may not reflect the overall picture of the country. It does not differ much from the results of similar studies at national level. However, this study can be a base for further studies in a broader perspective. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 103-110